PERAN RELIGIUSITAS DALAM MEMEDIASI PENGARUH KESADARAN HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK: (STUDI PADA KONSUMEN MUSLIMAH DI PEKANBARU PROVINSI RIAU) - Putriana Putriana (STAI Asy-Syukriyyah, 2022)
The increasing awareness of Muslim consumers about the importance of halal cosmetics will affect purchasing decisions for these products. For this reason, producers must convince consumers that the cosmetics they produce and sell are guaranteed to be halal. The purpose of this study was to determine the correlation between halal awareness, religiosity, and purchasing decisions. The methodology used in this research was quantitative with SEM-SmartPLS analysis tool. The study was conducted on 115 Muslim consumers in Pekanbaru, Riau Province with a purposive sampling procedure. The results of this study indicated that there is a positive influence of halal awareness on religiosity, a positive influence of religiosity on purchasing decisions, and the influence of halal awareness on purchasing decisions. Halal awareness can explain religiosity by 62.7% and has a strong correlation. Religiosity can explain purchasing decisions by 69% and also it has a strong correlation. The theoretical implication is that halal awareness and religiosity should be used as a theoretical basis and measure in purchasing decisions. The managerial implication is to prioritize raw materials, production processes and include halal labels on every cosmetic product produced.